Amitriptyline, Pregabalin and Duloxetine for Treatment of Painful Diabetic Peripheral Neuropathy - Nepal, Richa; Bajracharya, Manil Ratna; Karki, Budda Bahadur; Mall, Dipak; Shrestha, Prajaya Shikhar; Wasti, Kushal Prasad; Bisht, Anjal (Journal of Nepal Health Research Council, 2024)
Background: Painful diabetic peripheral neuropathy is one of the frequent presenting complaints in diabetes and endocrine clinics. Our main objective was to compare effectiveness of three commonly prescribed drugs: amitriptyline, pregabalin and duloxetine for treatment of painful diabetic peripheral neuropathy.Methods: This was a comparative, prospective, observational study conducted among 99 diabetic patients with painful diabetic peripheral neuropathy having numeric rating pain scale ? 4. Thirty-three patients in each group were consecutively prescribed amitriptyline, pregabalin and duloxetine in lower dose (10mg/75mg/20mg) for first two weeks to gradually up titrate to higher dose (25mg/150mg/30mg) as per pain response for total duration of eight weeks.Results: At the end of eight weeks, 84.9% in amitriptyline, 78.7% in pregabalin and 60.6% in duloxetine group had adequate pain reduction in form of mild or no pain. Among total patients, 42.5% patients had severe pain at baseline that decreased to 5% by the end of our study. Out of three drugs, 45.5% patients in amitriptyline group had complete resolution of pain as compared to 24.2% in pregabalin and 18.2% in duloxetine group (p value 0.05). Drowsiness (42.4%), dizziness (21.2%) and dry mouth (21.2%) were the commonest side effects among total participants in our study. Conclusions: Amitriptyline, pregabalin and duloxetine were all associated with adequate pain reduction among patients of painful diabetic peripheral neuropathy in our study, however, amitriptyline had more favorable findings with tolerable side effects. Keywords: Amitriptyline; duloxetine; Nepal; painful diabetic peripheral neuropathy; pregabalin.